BIOPRODUCTS PRODUCTION FROM VEGETABLE OIL RESIDUAL: CANDLE, CHALK AND MODELLING OF MASS - Thode Filho, Sérgio; Costa, Ana Paula da Silva da; Rodrigues, Israel; Sena, Marcelo Fonseca Monteiro de; Silva, Elmo Rodrigues da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The vegetable oil is a highly impactful reuse waste to the environment and have a high value even after consumption. The objective of this work is to obtain three alternative bioproducts such as mitigating the environmental impact caused by the improper disposal of waste vegetable oil. For production of the candle was used 50mL of residual vegetable oil and 40g of stearin, both were united into a cold beaker 200mL. For the production of chalk 10mL of residual vegetable oil, 20g stearine and 0.35g of pigment was used for sailing. Both states were cold in a 200mL beaker. For mass production model used was 12g wheat flour, 12g of corn starch, 6g of salt, 6g of calcium carbonate, 15mL of residual vegetable oil, 25mL of water, 2.25mL food coloring . The result of processing methodology is described in a material with acceptable physical properties without migrating oil, allowing be patterned and decorated. It was concluded that these bioproducts are advantageous from an economic and environmental perspective. Another important aspect is the use of waste materials in their composition which allows for extended cycle sold with these materials that would otherwise be discarded inappropriately or potential polluters of the environment and urban environment.